Riflessioni sulla ricerca didattica della Chimica: l’esempio del percorso sulla combustione nella scuola primaria - Fiorentini, Carlo (Chimica nella Scuola, 2025)
Taking the topic of combustion as an example, this contribution discusses the fundamental role of critical reflection on didactic experimentation, an aspect that is highly emphasized in terms of principles, but little analyzed and explored in its essential specific functions.